Petrie's Ptolemaic and Roman Memphis. - Ashton, Sally-Ann, author.
1 online resource
Keywords: "Memphis was one of the great melting pots of Mediterranean and African culture during the reigns of the heirs of Alexander and under the Roman Empire, a vibrant and complex community well after the end of the age of its ancient Pharaonic founders. For too long, its importance during this critical period has been wrongly eclipsed by the younger city of Alexandria. This book challenges such assumptions by taking a closer look at Memphis through the lens of the rich material excavated there by Flinders Petrie over a century ago, and exhibited in University College London?s Petrie Museum. These finds bring alive the diversity of the city?s inhabitants and raise questions, still relevant today, about the representations and realities of ethnic groups. This book presents the excavation background to the finds, their manufacturing processes and their cultural implications. It is accompanied by a CD ROM that illustrates this informative and neglected material."--Provided by publisher.